Changes in soil properties of a newly cleared Ultisol due to establishment of hedgerow species in alley cropping systems - Hulugalle, N.; Ndi, J. (Cambridge University Press, 1994)
This study was initiated to evaluate the short-term (< 3 years) ability of some selected acid-soil adapted hedgerow species when planted in alley cropping systems to improve soil properties in a newly-cleared Ultisol (Typic Kandiudult) of southern Cameroon, 1990–92. The hedgerow species selected were Senna (Senna spectabilis), Flemingia (Flemingia congesta)and Acioa (Acioa barterii). A non-alley-cropped control was also included in the trial. The greatest quantities of prunings, and hence, mulch were produced by Senna and Flemingia. Exchangeable Ca, effective CEC and water infiltration were greatly increased in the alleys of plots where either Flemingia or Senna had been planted within 2•5 years of hedgerow establishment. The large amounts of mulch produced by Senna and Flemingia did, however, result in soil temperatures greater than those of the control or Acioa plots c. 1 year after application of the prunings as mulch. Root growth of Senna in the subsoil was significantly greater than that of either Acioa of Flemingia, but that of cassava was reduced by alley cropping with all three hedgerow species. Compared to the control or alley cropping with Acioa, maize and cassava yields were greater when alley cropped with either Flemingia or Senna hedgerows.